Trust and Organizational Culture as a Driver of Relational Capital to Organizational Performance in BPJS Ketenagakerjaan Surabaya Region - Dhiya Agung Priambodo; Gendut Sukarno (International Journal of Business and Applied Economics, 2023)
This study aims to determine trust and organizational culture as drivers of Relational Capital and organizational performance in the BPJS Ketenagakerjaan Surabaya region. This study was conducted at the company BPJS Ketenagakerjaan Surabaya region with a total population and a sample of 50 employees. The Data in this study is the primary data obtained through interviews, questionnaires, and observations. Data analysis and analysis tools used in this study are Structural Equation Modeling and Partial Least Squares analysis tools. The results of this study indicate that both Trust and organizational culture are able to influence Relational Capital so that it can drive organizational performance. Improved organizational performance is evidenced by the higher level of trust participants have in the organization, the good organizational culture, and the establishment of a good level of Relational Capital.